Fasciola hepatica infection reduces Mycobacterium bovis burden and mycobacterial uptake and suppresses the pro‐inflammatory response. (20th June 2016) - Garza‐Cuartero, L.; O'Sullivan, J.; Blanco, A.; McNair, J.; Welsh, M.; Flynn, R. J.; Williams, D.; Diggle, P.; Cassidy, J.; Mulcahy, G.
Summary: Bovine tuberculosis (BTB), caused by Mycobacterium bovis, has an annual incidence in cattle of 0.5% in the Republic of Ireland and 4.7% in the UK, despite long‐standing eradication programmes being in place. Failure to achieve complete eradication is multifactorial, but the limitations of diagnostic tests are significant complicating factors. Previously, we have demonstrated that Fasciola hepatica infection, highly prevalent in these areas, induced reduced sensitivity of the standard diagnostic tests for BTB in animals co‐infected with F. hepatica and M. bovis . This was accompanied by a reduced M. bovis ‐specific Th1 immune response. We hypothesized that these changes in co‐infected animals would be accompanied by enhanced growth of M. bovis . However, we show here that mycobacterial burden in cattle is reduced in animals co‐infected with F. hepatica . Furthermore, we demonstrate a lower mycobacterial recovery and uptake in blood monocyte‐derived macrophages (MDM) from F. hepatica‐ infected cattle which is associated with suppression of pro‐inflammatory cytokines and a switch to alternative activation of macrophages. However, the cell surface expression of TLR2 and CD14 in MDM from F. hepatica ‐infected cattle is increased. These findings reflecting the bystander effect of helminth‐induced downregulation of pro‐inflammatory responses provide insights to understand host‐pathogen interactions in co‐infection.